Adherence to COVID-19 appropriate behaviour among small scale workers in unorganized sector in Rajasthan by applying health belief model and generalized social beliefs - Kumar, Ashok; ., Praveena; Tiwari, Pradeep K.; Barik, Rashmi R. (International Journal Of Community Medicine And Public Health, 2021)
Background: People’s adherence to COVID-19 appropriate behavior (CAB) is important to prevent and manage coronavirus disease-19. The study aimed to determine the prevalence and associated factors of adherence to CAB in small-scale workers in the unorganized sector by applying health belief model (HBM) and generalized social beliefs. Methods: This community-based, cross-sectional study was done in Central Rajasthan from January 2021 to March 2021. A pre-tested, structured, interviewer-administered tool was used to collect data from 384 participants. Data were collected on five constructs of HBM and two social axioms. Results: The mean (SD) age of participants was 36.89 (10.84) years. About 58% of participants were male. Adherence to all CAB measures was 15%, it was not found to be associated with age, gender, education level, residence and occupation. The most common practiced CAB measure was face cover (57.8%) followed by handwashing (43.75%). Adherence was found associated with all five HBM constructs and two social axioms. Conclusions: The adherence to CAB was low among small-scale workers in the unorganized sector. It is pivotal to consider the community’s perceived susceptibility, severity, benefit, barrier, cue to action, cynicism and reward for application to improve the adherence towards CAB.